Tinjauan Hukum Islam terhadap Pinjaman Kredit Usaha Masyarakat di Unit BUMDes “Loh Jinawi” Desa Candipari Kecamatan Porong Kabupaten Sidoarjo - Faruq, Muhammad Al; Masduqie, Muhammad Hamdan Ali; Djalaluddin, Ahmad Ahmad (Sharia Faculty Islamic Economic Law Study Department, 2023)
Mu'amalah in the Islamic context requires fellow human beings to cooperate and relate to each other to increase benefit and not cause harm to each other. The debt receivables agreement is intended to help each other among fellow human beings, tosolvean problem and facilitate the continuity of hislife. The purpose of this study is to analyze the borrowing of community business loans in the BUMDes unit